Am I outdated? The role of strengths use support and friendship opportunities for coping with technological insecurity. (June 2020) - Goetz, Tim M.; Boehm, Stephan A.
Abstract: In the digital era, the prevalent integration of new technologies in work processes gives rise to employees' perceptions of technological insecurity. Such technology-induced strain poses new challenges to occupational health and safety and needs to be better understood in order to be prevented. Based on Conservation of Resources (COR) theory, we investigate to which extent the negative effect of technological insecurity on perceived health depends upon the availability of non-technology-related resources in the workplace. Specifically, we argue that employees who experience two key organizational resources, i.e. organizational support for strengths use and friendship opportunities, are better suited to cope with these modern forms of strain. We hypothesize that those resources reinforce each other in such way that employees' coping capabilities rise and health issues decrease. For hypothesis testing, time-lagged hierarchical moderated regression analysis is conducted. The study sample consists of 8019 German employees. Results support our assumption that accumulating resources create an intensified buffering effect, which surpasses the additive buffering effects of individual resources. Under the condition of high support for strengths use and high friendship opportunities, technological insecurity does no longer show a negative relationship with employees' time-lagged health. By using post-stratification weights, these results apply to 33.3 million employees in Germany having access to Information and Communication Technologies. Highlights: COR theory is offered as a new theoretical lens to investigate effects of technostress. Technological insecurity threatens employees' general health. We propose support for strengths use and friendship opportunities as buffering resources. If both resources are highly available, technological insecurity is unrelated to health. Population-representative data of the German workforce support the theoretical model.